An Analysis of Employees’ Emotion and Communication at UPT SDA V Tangerang District Banten Indonesia - MANNAN, AROSYID; *, Enawar; *, Abdurrosyid; Nabawi, Muhamad (IJRDO - Journal of Social Science and Humanities Research, 2018)
Emotion and communication are two issues that are very individual and private as in the work environment, each employee has different emotion control and  ommunication skills. Many factors that can determine both such as type and workload of employees in at office and at field. This research is intended to find out the differences of emotion types and communication modes between office employees and field employees at UPT SDA V Tangerang District. The method used in this research is a qualitative method; the research data can be obtained thorugh surveys distributed to all employees in UPT SDA V. The results state that there is no difference of the type of emotion and communication modes between office employees and field employees, the initial assumption that office employees are more able to control their emotions than field employees is not proven, as well as the communication skills of office employees assumed to be better than those of field employees is also not justified.